Tuberculosis Diagnosis in HIV-Infected Children: Comparison of the 2012 and 2015 Clinical Case Definitions for Classification of Intrathoracic Tuberculosis Disease. Issue 3 (13th December 2021) - Marcy, Olivier; Goyet, Sophie; Borand, Laurence; Msellati, Philippe; Ung, Vibol; Tejiokem, Mathurin; Do Chau, Giang; Ateba-Ndongo, Francis; Ouedraogo, Abdoul Salam; Dim, Bunnet; Perez, Paul; Asselineau, Julien; et al.
Abstract: Background: There is no gold standard for tuberculosis diagnosis in children. Clinical Case Definitions for Classification of Intrathoracic Tuberculosis in Children were proposed by international experts in 2012 and updated in 2015. We aimed to compare the 2012 and 2015 Clinical Case Definitions in HIV-infected children with suspected tuberculosis. Methods: We enrolled HIV-infected children with suspected tuberculosis in Burkina Faso, Cambodia, Cameroon, and Vietnam (ANRS [Agence Nationale de Recherches sur le SIDA et les hépatites virales] 12229 PAANTHER [Pediatric Asian African Network for Tuberculosis and HIV Research] 01 Study). We classified children using the 2012 and 2015 Case Definitions considering as tuberculosis cases those with confirmed tuberculosis and those with probable and unconfirmed tuberculosis in the 2012 and the 2015 classifications, respectively. We assessed agreement between both classifications. Results: Of 438 children enrolled, 197 (45.0%) children were classified as tuberculosis (45 confirmed, 152 probable) using the 2012 Case Definition and 251 (57.3%) were classified as tuberculosis (55 confirmed, 196 unconfirmed) using the 2015 classification. Inter-classification agreement for tuberculosis diagnosis was 364/438, 83.1%, with a kappa statistic of 0.667 (95% confidence interval 0.598-0.736). Of 152 children with probable tuberculosis (2012), 142 (93.4%) were considered as tuberculosis by the 2015 version and 10 (6.6%) as unlikely tuberculosis including 9 with spontaneous clinical improvement. Of 132 possible tuberculosis (2012), 58 (43.9%) were reclassified as tuberculosis (2015). Conclusions: Agreement between the 2 versions of the Case Definition was substantial but more children were considered as tuberculosis using the 2015 version. Spontaneous symptom resolution reinforces both confidence in the "unlikely" category as being children without tuberculosis and the importance of the clinician's treatment decision in the study. Abstract : We compared the 2012 and 2015 Clinical Case Definitions for Classification of Intrathoracic Tuberculosis in Children in 438 HIV-infected children with presumptive tuberculosis. Agreement between the classifications was substantial but more children were considered as tuberculosis using the 2015 version.